The darkest evening of the year - Koontz, Dean R. (New York : Bantam Books, 2007)
Amy Redwing has dedicated her life to the southern California organization she founded to rescue abandoned and endangered golden retrievers. No one is surprised when Amy risks her life to save Nickie, nor when she takes the female golden into her home. The bond between Amy and Nickie is immediate and uncanny. Even her two other goldens, Fred and Ethel, recognize Nickie as special, a natural alpha. But the instant joy Nickie brings is shadowed by a series of eerie, ominous, and invasive incidents.--From publisher's description.
Keywords: Dog rescue -- Fiction; Golden retriever -- Fiction